Effect of Intermittent Fasting on Decreased Interleukin-6 Genes mRNA Expression in Mice (Mus Musculus) - Herman, Sriyana; Muhammad Basir; Mochammad Hatta; Suryani As’ad; Ilhamjaya Patellongi; Ahmad Hadi Modi (Indonesian Andrology and Biomedical Journal, 2024)
Nowadays, the development of various degenerative diseases is very rapid. The rapid development of the disease has encouraged the wider community to understand the impact. Intermittent fasting can help prevent the emergence of cancer (one of the degenerative diseases) because during fasting the body's cells are in protective mode so as to protect the body from disease. Intermittent fasting reduces the body's inflammatory status by inhibiting the expression of proinflammatory cytokines, especially interleukin-6 (IL-6). This study aims to examine the effect of intermittent fasting on IL-6 gene mRNA expression. This study is an experiment with Pretest-Posttest with Control Group design to examine the effect of intermittent fasting on the of IL-6 genes mRNA expression. The subjects of this study were 10 mice divided into 2 groups: the intermittent fasting group and the control group. The research was carried out at the Laboratory of Molecular Biology and Immunology Department, Faculty of Medicine, Universitas Hasanuddin, Makassar, as a place for the maintenance and care of experimental animals as well as examination of IL-6 genes mRNA expression. The study was conducted for 30 days. The results showed a decrease in the average value of IL-6 mRNA expression of subjects before and after intermittent fasting with the value of ρ = 0.003 (ρ <0.05) showed that there is a significant effect between intermittent fasting on the decrease in IL-6 genes mRNA expression. In conclusion, there is a decline in the IL-6 genes mRNA expression after intermittent fasting.